Perfil da população atendida e notificada por tuberculose em um hospital escola de 2010 a 2014 - Santos, Mariana Bertolino Fioramonti dos (2016)
Tuberculosis (TB) is an infectious disease of chronic development, which mainly affects the lungs and it is caused by Mycobacterium tuberculosis. Currently it remains on the list of health problems both at the global level, as the national. According to the World Health Organization estimated that in 2014 there were 9.6 million people sick with tuberculosis in the world. In 2014 they were diagnosed in Brazil 67,966 new cases of tuberculosis, heterogeneously distributed in the Federative Units and the Federal District, with average incidence rate around 33.5 cases per 100 thousand inhabitants. The State of São Paulo has rates around 36.9 cases / 100,000 inhabitants, in addition, it is important the incidence of the disease on populations of lower economic and social power. In 2014, in the city of São José do Rio Preto were reported 136 cases of tuberculosis with an incidence of 32.7 cases per 100 thousand inhabitants, rate lower than the national average, but very significant for the region. Objectives: Analyze the sociodemographic and epidemiological characteristics and identify the factors associated with TB patients reported in Hospital School in São José do Rio Preto. Materials and methods: This is a descriptive and retrospective study performed transversely held in a hospital in the state of São Paulo, from January 2010 to December 2014. Data were collected from the reporting forms of cases of TB for Epidemiological Surveillance Center of the service. The population was submitted to the pairing process records followed by purification of duplicate records. The data were stored in spreadsheets, through these data were constructed tables and frequency graphs. Qualitative data were associated through the application of Chi-Square test and quantitative data were compared using the Kruskal-Wallis test with subsequent application of the multiple comparison test of Dunn. It performed multiple correspondence analysis and all statistical tests were applied with a 0.05 significance level. The software used for analysis were Minitab 17 (Minitab Inc.) and Statistica 10 (StatSoft Inc.).Results: The data show that the socio-demographic and epidemiological aspects of tuberculosis incidence in the population is consistent with most studies in other regions, the hospitalization data was shorter compared to other research. It was also observed that there is a strong association between the population affected by TB and HIV coinfection. Conclusion: The results of study represent the most susceptible people to TB infection in the area, with no great differences between the world known population. The co-infection of TB / HIV must remain as a constant research target, especially because of the immense mortality of these individuals.